Optimizing Employee Engagement to Improve Human Resources Performance: A Case Study of A Private University in Facing the VUCA Era - Hermawan, Rudianto (Technium Social Sciences Journal, 2020)
As educational service providers, universities play a major role in the success of government programs, namely the intellectual life of the nation. Higher education must be able to manage human resources well because it will have an impact on the effectiveness of the organization’s work. The purpose of this study was to find answers on how to optimize employee engagement to improve the performance of human resources (HR) in tertiary institution in the VUCA era and what factors should be prioritized for improving human resources in a university in the VUCA era. This study applies a case study approach from qualitative research design. In this study a semi-structured interview is used to get the perspectives of employee engagement. The research proved that to optimize employee engagement in higher education, an institution must be able to understand the difficulties faced by its employees. An institution must also be able to provide motivation and support to all employees so that they will feel comfortable and safe at work and this can prevent performance deterioration.